Analisis Keterampilan Menulis Puisi Anak di SD Negeri Ciremai Giri - Lailiyah, Alina Nur; Priyanti , Intanika Maya; Lestari, Sri (Caruban: Jurnal Ilmiah Ilmu Pendidikan Dasar, 2024)
This research aims to determine the skills of fourth grade students at SD Negeri Ciremai Giri in writing children's poetry based on aspects of typography, rhyme, diction, imagery, figures of speech (language style) and clarity of content. This research uses descriptive qualitative research. The research subjects consisted of 22 fourth grade students at Ciremai Giri State Elementary School. Based on the research that has been carried out, the results of the analysis are that in the typographic aspect of poetry writing students received a high category with an average percentage of 55%, in the rhyme section it showed an average percentage of 36% which was included in the low category. The diction aspect shows an average percentage of 47% in the sufficient category. The image aspect with a percentage of 41% is in the quite good category. In the figure of speech aspect, they got an average of 41% in the sufficient category. In terms of content clarity, the average is 66% in the high category. Based on the results of the analysis, poetry writing skills have reached quite good skills. However, students have difficulty implementing rhyme elements in writing poetry. The difficulty of Ciremai Giri State Elementary School students in implementing rhyme is caused by several factors, including immature understanding of the concept, limited vocabulary, and difficulty in identifying rhyme patterns.